(untitled) (NAU Journal of Library and Information Science, 2019)
Right to freedom of expression is protected and enjoyed in civilized and democratic societies. Yet, the reality is that this right is by no means absolute anywhere in the world as it is riddled with a number of restrictions and derogations. One of such derogations is provided by the law creating the offence of sedition. This paper exposed the relationship between the right to freedom of expression and the crime of sedition. The paper found that no society can function effectively without the guarantee of the right to freedom of expression. It also discovered that the exercise of this right can be curtailed in the interest of public peace, order, morality, security and sovereignty of the state. The methodology adopted in this study was essentially doctrinal involving the analysis of the primary and secondary sources used. In order to strike a balance, the study identified the need to amend section 51 (1) and (2) of the Criminal Code to ensure that a conviction under the section would only be allowed where the conduct of the accused lends itself to incitement of violence and of course where the requisite mens rea is established. The paper further recommends amendment of relevant provisions of the Criminal Code in order to accommodate adequate punishment in deserving circumstances in view of the heinous harm done to the fabric of society by seditious publications/comments. It further strongly recommended that any form of limitation period be removed in relation to the prosecution of sedition since ‘time does not run against the state.